Analisis Kekakuan Pada Pelat Baja Galvanil 0.8mm Akibat Pembentukan Dingin Dengan Metode Bead Rolled Variasi Ukuran Dan Bentuk Radius - Avriyansah, Illham; Erwanto, Erwanto (Manutech : Jurnal Teknologi Manufaktur, 2025)
Cold plate forming process is widely used and needed in manufacturing industries such as automotive industry. One of the cold plate profile forming processes is by plate roll process or often called "Bead Roll". The bead roll process is widely used because the process is cheap, but is able to improve/add good vibration resistance, "Bead Roller" machine functions to make curves or profiles on the plate sheet. The resulting profile produced by this machine is collected and analyzed using the Taguchi method, which is a statistical data processing technique that aims to find the best final profile. The best damping result is a plate with a roll eye width of 12 mm and a rolling depth of 5 mm. The results of this study are expected to expand knowledge about plates used as new form innovations and become a reference for future research and development.